A switchable peroxidase mimic derived from the reversible co-assembly of cytochrome c and carbon dots. Issue 12 (4th March 2016) - Essner, Jeremy B.; McCay, Richard N.; Smith II, Chip J.; Cobb, Stephen M.; Laber, Charles H.; Baker, Gary A.
Abstract : We describe a straightforward tactic to boost the inherently low peroxidase-like activity of the heme-protein equine cytochrome c following its electrostatic assembly onto the carbon nanodot surface. Abstract : We describe a straightforward tactic to boost the inherently low peroxidase-like activity of the heme-protein equine cytochrome c (cyt c ) following its electrostatic assembly onto the carbon nanodot surface. This represents the first time that carbon nanodot interaction has been demonstrated to switch a protein into a high-performance enzyme for speeding up a reaction it was not evolved to catalyze. The dramatic enhancement in peroxidase-like activity stems in part from favorable local perturbations within the heme microenvironment of cyt c which are influenced by the chemistry presented at the carbon dot surface. That is, the observed peroxidase activity is clearly moderated by the choice of molecular precursors used to prepare the carbon dots, a choice which ultimately determines the surface charges present. An exceptional catalytic efficiency ( k cat / K M ) of 8.04 (±1.74) × 10 7 M −1 s −1 was determined for carbon dot/cyt c co-assemblies, close to the theoretical diffusion-controlled limit. Notably, the activity of the carbon dot/cyt c assembly can be switched off simply by increasing the ionic strength which results in dissociation into non-catalytic components.